A fine balance - Mistry, Rohinton, 1952- (2001)
A portrait of India featuring four characters. Two are tailors who are forcibly sterilized, one is a student who emigrates, and the fourth is a widowed seamstress who decides to hang on. A tale of cruelty, political thuggery and despair by an Indian from Toronto, author of Such a Long Journey.
Keywords: India -- History -- 1947- -- Fiction